(untitled) (IITM Journal of Business Studies, 2025)
Regardless of the Integrated Fish Farming System (IFFS) being more economical and sustainable, its adoption has not been commendable, especially in developing countries like India. In light of these concerns, the current study attempts to understand the barriers to the adoption of IFFS. In addition to the variables of constraints identified through previous literature, other variables were identified and selected by conducting FGDs with experts from the College of Fisheries, Raha, Assam. A total of 504 farmers were chosen for the study using multi-stage sampling approaches in twelve districts that included all six of Assam’s Agro-Climatic Zones. Analyzing the data with SPSS, both descriptive and inferential statistics were employed in comprehending the data. To reduce the dimensions of restrictions, Principal Component Analysis (PCA) was used in conjunction with Exploratory Factor Analysis (EFA). Using varimax rotation, the Factor Analysis Model resulted in seven factors of constraints. The model has been found to have a good fit with an acceptable non-residual value. The assessment of such constraints does not only provide a helping hand in disseminating such sustainable agricultural practices but also ensures the sustainable usage of farm waste by making ecological considerations.